A critique study on phase optimized generalized discrete fourier transform based partial transmit sequence for PAPR in OFDM systems - Habaebi, Mohamed Hadi; Budalal, Asma. Ali H.; Awad, Abdallah M. A.; Ali, Ismail M.; Youssouf, Abdouraouf S.; Hameed, Shihab A. (Asian Research Publishing Network (ARPN), 2015)
Orthogonal Frequency Division Multiplexing (OFDM) is a revolutionary digital modulation technique which known as a next generation of wireless communication 5th Generation. OFDM supports high speed data rate and multi user technique where it can accommodate large number of users showing spectral efficiency to meet the fast growing demands for better throughput and quality of service. However, OFDM-time domain signal suffering from a large peak-to-average power ratio PAPR .Fortunately several schemes have been proposed to reduce the problems of PAPR. One of the effective methods is partial transmit sequence PTS with pseudo-random sub-blocks portioning as it has better PAPR performance. Many techniques introduced to improve the performance of PTS scheme. In this paper a critique study on the use of phase optimized from the theory of generalized discrete Fourier transform GDFT is carried out. this method, generates nonlinear phase to OFDM sub blocks after taken of IFFT for each sub block, then the output phase is rotated by coefficients depending on number of side information bits ‘m’ to produces minimum PAPR. Simulation results elaborate that phase modification of OFDM frames before applying PTS that has achieved acceptable reduction in both complexity and PAPR.